De l’enjeu de conservation au projet de territoire : Le saumon atlantique au coeur des débats - Olivier Thomas; Marie-Anne Germaine (VertigO)
The implementation of actions in favour of the conservation or of the restoration of the biodiversity often leans on the highlit of symbolic species attached to a biotope regularly presented as a heritage. Concerning the water environment, and quite particularly as regards the assertion of the principles of ecological management mobilizing the restoration of the ecological continuity of streams, the Atlantic salmon is one of the main migratory amphihalins fishes used to make sensitive the decision-makers, the financiers and the general public. In this article, the objective is to wonder about the place of this « not human » actor in the construction of programs with ecological aim such as the removal of dams. The analysis joins two scales : that of the national and European strategies intended to restore the stocks of salmons, and that of a local project of dismantling of dams in the valley of Selune (Manche). By this way, the objective is to put in mirror the ecological challenge of preservation of the species with the local reality of a project of new arrangement of a stream in a territory. In fine, this article demonstrates that the instrumentalization of the salmon can turn out to be a wrong path for the species but also for the deployment of the water-related environmental policies.